Comparative study on the weight loss and lipid metabolism by tea polyphenols in diet induced obese C57BL/6J pseudo germ free and conventionalized mice - Kashif Hussain; Yingying Yang; Jie Wang; Hengjuan Bian; Xi Lei; Junjie Chen; Qianying Li; Li Wang; Qingping Zhong; Xiang Fang; Yutao Wang; Hong Wei; et al. (Food Science and Human Wellness)
The role of gut microbiota in terms of host health is becoming increasingly important. In this study, the comparative effects of tea polyphenols (TPs) on weight loss and lipid metabolism on conventionalized mice (CVZ) and pseudo germ-free (PGF) mice (treated with antibiotics) were investigated. Our findings revealed that high fat (HF) diet considerably increased the body weight, total fat and upsurge lipid indices in CVZ mice but PGF mice were not sensitive to the effect of HF diet as CVZ mice. After the dietary administration of TP, body weight, perirenal fat and epididymal fat, liver weight, glucose (GLU) level, total chloestrol (TC level), high density lipoprotein-cholesterol (HDL-C) level significantly lowered in PGF mice as compared to CVZ mice group. However, the area of fat cells and triglyceride (TG) level were significantly increased in PGF mice. In CVZ mice, TP intervention resulted in a considerable drop in the Firmicutes/Bacteroides ratio as compared to PGF mice. The intestinal flora of PGF mice was severely reduced after antibiotic treatment, while TP administration restored intestinal diversity; the abundance of Akkermansia and Lactobacillus increased, whereas the abundance of Enterobacteriaceae and Prevotella reduced. Overall, we can assume that PGF obese mice administered with TP have less anti-obesity effects compared to obese CVZ mice.